2010
DOI: 10.1089/rej.2009.0934
|View full text |Cite
|
Sign up to set email alerts
|

Is Lipid Peroxidation of Polyunsaturated Acids the Only Source of Free Radicals That Induce Aging and Age-Related Diseases?

Abstract: The increase in free radicals is hypothesised to cause aging and age-related diseases. The most common source of free radicals is thought to be superoxide. This superoxide is claimed to be released from mitochondria during the enzymatic transformation of oxygen to water by a "leakage" process. This article presents evidence that leakage does not occur. Instead, protonated superoxide radicals are generated by lipid peroxidation processes. In nature, polyunsaturated fatty acids (PUFAs) represent particularly oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 157 publications
2
27
0
3
Order By: Relevance
“…In fact, the non-enzymatic peroxidation is a known process (Niki et al 2005), mainly involving unsaturated fats (Spiteller 2010), being further enhanced in our experiments, due to the culture medium incubation in the presence of atmospheric oxygen (21 %). The concentration of the five studied HETE did not significantly change in the three culture media used (basal, adipogenic and osteogenic) after incubation in the presence of AA without cells.…”
Section: Discussionmentioning
confidence: 72%
“…In fact, the non-enzymatic peroxidation is a known process (Niki et al 2005), mainly involving unsaturated fats (Spiteller 2010), being further enhanced in our experiments, due to the culture medium incubation in the presence of atmospheric oxygen (21 %). The concentration of the five studied HETE did not significantly change in the three culture media used (basal, adipogenic and osteogenic) after incubation in the presence of AA without cells.…”
Section: Discussionmentioning
confidence: 72%
“…This hyperbaric therapy was subsequently proven to impact the production of ROS, resulting in the clouding of the crystalline lens in newborns 3,4. Oxidative stress has since been correlated with several pathological or physiopathological conditions, including type 2 diabetes mellitus 3,4, senescence 5, 6, cardiovascular disease 7-11, cancer 12-14, pulmonary disease 15, 16, and hepatopathies 15, 16. However, to date, no study has investigated the link between oxidative stress and diseases of endodontic origin.…”
Section: Introductionmentioning
confidence: 99%
“…ROS are formed as natural byproducts of oxygen metabolism and by enzymatic activity. In both cases, ROS production is highly localized and spatially restricted which makes it a efficient system for cell signaling processes such as glucose transport(Chambers, Moylan, Smith, et al, 2009), eicosanoid (Spiteller, 2010) and cytokine production (Sigala et al, 2011), and mitochondrial biogenesis (Austin, Klimcakova, & St-Pierre, 2011; Kang & Li Ji, 2012). However, during times of environmental stress (e.g., UV or hyperthermia), metabolic stress (e.g., hyperglycemia), or in disease states (e.g., muscular dystrophy, unloaded diaphragm during mechanical ventilation) ROS levels can increase dramatically resulting in aberrant signaling(D.…”
Section: Reactive Oxygen Signaling and The Ros Paradoxmentioning
confidence: 99%
“…For example, oxidation, Snitrosylation (Foster, McMahon, & Stamler, 2003; Sun, Xin, Eu, Stamler, & Meissner, 2001), or S-glutathionylation of key cysteine in the RyR1 calcium release channel of skeletal muscle can significantly alter the mean open time and the permeability of the channel (Aracena-Parks et al, 2006; Hamilton & Reid, 2000; Hidalgo, et al, 2006). In addition to the RyR1, the sarcoendoplasmic reticulum calcium ATPase pump (i.e., SERCA pump) (Lehotsky, Kaplan, Murin, & Raeymaekers, 2002; Squier, 2001; Trebak, Ginnan, Singer, & Jourd'heuil, 2010) membrane lipids (Spiteller, 2010), or DNA (Ragu et al, 2007), CaMKinase (Franklin, Rodriguez–Mora, LaHair, & McCubrey, 2006; Pinto, de Sousa, & Sorenson, 2011) and contractile proteins(Ferreira, et al, 2012; Stasko, Hardin, Smith, Moylan, & Reid, 2013) have all been shown to be modified by ROS/RNS.…”
Section: Targets Of Ros/rns In Skeletal Musclementioning
confidence: 99%